Inovasi Usaha Abon Lele Tingkat Usaha Kecil Menengah (UKM) dalam Peningkatan Kualitas Produk - Anam, Choirul; Harini, Harini; Widiyanti, Emi (Universitas Negeri Yogyakarta, 2022)
Industrial development in Indonesia is very dynamic, including in the food and beverage industry. So that innovation and facilitation for Small and Medium Enterprises (SMEs) are needed to improve the competitiveness of the products produced. SMEs shredded catfish